The Paris Declaration in practice: challenges of health sector aid coordination at the district level in Zambia - Sundewall Jesper; Forsberg Birger C; Jönsson Kristina; Chansa Collins; Tomson Göran (BMC, 2009)
Abstract Background The increasing resources available for and number of partners providing health sector aid have stimulated innovations, notably, the Paris Declaration on Aid Effectiveness, which aim to improve aid coordination. In this, one of the first studies to analyse implementation of aid coordination below national level, the aim was to investigate the effect of the Paris Declaration on coordination of health sector aid at the district level in Zambia. Methods The study was carried out in three districts of Zambia. Data were collected via interviews with health centre staff, district managers and officials from the Ministry of Health, and from district action plans, financial reports and accounts, and health centre ledger cards. Four indicators of coordination related to external-partner activity, common arrangements used by external partners and predictability of funding were analysed and assessed in relation to the 2010 targets set by the Paris Declaration. Findings While the activity of external partners at the district level has increased, funding and activities provided by these partners are often not included in local plans. HIV/AIDS support show better integration in planning and implementation at the district level than other support. Regarding common arrangements used for fund disbursement, the share of resources provided as programme-based support is not increasing. The predictability of funds coming from outside the government financing mechanism is low. Conclusion Greater efforts to integrate partners in district level planning and implementation are needed. External partners must improve the predictability of their support and be more proactive in informing the districts about their intended contributions. With the deadline for achieving the targets set by the Paris Declaration fast approaching, it is time for the signatories to accelerate its implementation.